Transposition of the pedicled radial forearm flap to reconstruct an electrical burn defect of the hand - A. V. Sachkov; S. V. Smirnov; M. A. Migunov; Yu. V. Stepanova; M. A. Litinskiy (Трансплантология (Москва), 2016)
According to statistics, from 9 to 15 patients with electrical injury or electrical burn were annually admitted to the Burn Center of N.V. Sklifosovsky Research Institute for Emergency Medicine in the period from 2012 to 2015 that made about 1.5% of the total number of patients. The electrical injury, being a most severe and socially devastating injury, requires using combined therapies, applying the techniques of plastic and reconstructive microsurgery. The Burn Center specialists have developed up-to-date reconstructive techniques to quickly and efficiently treat tissue defects, including those after electrical burns.